Two-week-wait referrals in otolaryngology in a tertiary centre: cross-sectional study of benign outcomes, with a systematic review. Issue 11 (3rd November 2022) - Mettias, B; Charlton, A; Ashokkumar, S
Abstract: Objective: The two-week-wait referral is designed to improve early detection in cancer patients. This retrospective study analysed those ENT two-week-wait referrals to out-patient clinics in a tertiary head and neck oncology centre, from January to June 2018, which were not compliant with National Institute for Health and Care Excellence guidelines (2015 update). Methods: Referral symptoms were statistically analysed against National Institute for Health and Care Excellence guidelines, with detailed analysis of reasons for non-compliance. In addition, a systematic review of similar previously published articles was conducted. Results: There were 1107 patients referred through the two-week-wait pathway. Of these referrals, 52 per cent were compliant with National Institute for Health and Care Excellence 2015 guidelines. Six errors were identified for non-compliant referrals, most commonly inconsistencies in referral (e.g. globus sensation) and intermittent disease course (e.g. intermittent hoarseness). Of all patients referred, 93 per cent were diagnosed with benign conditions, with laryngopharyngeal reflux being the commonest. Twenty-two per cent of referred patients were discharged after the first visit. Conclusion: Two-week-wait referral is inappropriately overused. There are many non-compliant referrals, and most of the outcomes are benign.